Boys and girls learn differently! : a guide for teachers and parents - Gurian, Michael; Henley, Patricia, 1944-; Trueman, Terry (San Francisco : Jossey-Bass, 2001)
A thoroughly revised edition of the classic resource for understanding gender differences in the classroomIn this profoundly significant book, author Michael Gurian has revised and updated his groundbreaking book that clearly demonstrated how the distinction in hard-wiring and socialized gender differences affects how boys and girls learn.
Includes bibliographical references and index
Keywords: Sex differences in education -- United States -- Case studies; Educational change -- United States -- Case studies